Formulation, characterisation and antibacterial activity of lemon myrtle and anise myrtle essential oil in water nanoemulsion. (15th July 2018) - Nirmal, Nilesh Prakash; Mereddy, Ram; Li, Li; Sultanbawa, Yasmina
Highlights: The required HLB value for LM EO and AM EO are 14 and 12, respectively. The smallest droplet size of 16.07 nm (LMEO) and 30.23 nm (AMEO) was obtained. The selected nanoemulsions of LMEO and AMEO were transparent. The selected nanoemulsion of LMEO and AMEO had good stability at 4, 25 and 40 °C. Nanoemulsion improved antibacterial activity of LMEO. Abstract: This study focussed on the formulation, characterisation of lemon myrtle (LM) and anise myrtle (AM) essential oil (EO) in water nanoemulsion and their antibacterial activity. The required hydrophilic lipophilic balance (rHLB) value of LM EO and AM EO was 14 and 12, respectively. The Central Composite Rotatable Design (CCRD) model produces the smallest droplet size and polydispersity index (PDI) for LMEO (d ≈ 16.07 nm; PDI ≈ 0.209) and AMEO (d ≈ 30.23 nm; PDI ≈ 0.216) at 1% EO and 10% surfactant mixture (Smix) ratio using ultrasonication for 5 min. Whereas, increased in EO, decrease in Smix concentrations and ultrasonication time produces higher droplet size of nanoemulsions. LMEO (LM-15, LM-17) nanoemulsions was clear and transparent compared to AMEO (AM-15, AM-17). All the selected nanoemulsions showed good stability at 4, 25 and 40 °C during storage, except LM-15 at 40 °C. LMEO nanoemulsion showed enhanced antibacterial activity compared to LMEO alone (P < 0.05).